The Impact of the Quality of Services, Price and Promotion on the Consumer Satisfaction at BC Street Coffee Denpasar - MERTHAYASA, I MADE PUTRA AKEN; USTRIYANA, I NYOMAN GEDE; ANGRENI, IGA.A LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.2, April 2019DO - 10.24843/JAA.2019.v08.i02.p12, 2019)
The Impact of the Quality of Services, Price and Promotion on the Consumer Satisfaction at BC Street Coffee Denpasar The annual increase in the contribution made by the trading sector and hotel and restaurant sector has caused the restaurants in Denpasar, including the BC Street Coffee, to be getting more competitive. It is necessary to analyze the factors, such as the quality of services, price and promotion, which contribute to the consumer satisfaction. This current study is intended to identify the characteristics of the respondents, the quality of services, price and promotion on the consumer satisfaction. The study was conducted from March to May 2018. The respondents totaled 50. The data were analyzed using the validity test, reliability test, multiple linier analysis, classic assumption test, hypothesis test, and descriptive analysis. The dominant consumers of the BC Street Coffee were from 18 to 25 years old, male, senior high school graduates, private employees and single. They felt highly satisfied with the quality of services, price and promotion provided. Partially and simultaneously, the quality of services, price and promotion significantly contributed to the consumer satisfaction. The R Square showed that the quality of services, price and promotion contributed to the consumer satisfaction by 62%, and the rest, namely 38%, was affected by the other variables. It is suggested that the BC Street Coffee should always pay attention to what is desired and needed by the consumers and the price of the product offered. It is suggested to the future researchers that they add other variables and another object under a particular territory.